STUDI TENTANG PELAYANAN MINAT BACA PERPUSTAKAAN KELILING PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN BARITO TIMUR (Studi Kasus pada SDN 1 Tamiang Layang, SDN 1 Hayaping dan SDN Janah Mansiwui) - Salim, M. Hasbi; Warsito, Yellintiani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the quality of mobile library services provided by the East Barito Regency Library and Archives Office and to analyze factors influencing elementary school students' reading interest. Mobile library services are considered a strategic tool for enhancing literacy in areas lacking permanent library facilities. This study employed a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. A purposive sampling method was used to select informants, with a total of 18 informants. The results indicate that mobile library services in East Barito Regency still face various challenges, such as limited book availability, irregular visiting hours, and a shortage of staff. However, student enthusiasm for this service is quite high. Factors influencing reading interest include accessibility to books, the personal approach of staff, and support from the school. This study recommends increasing the number and variety of book collections, scheduling more regular visits, and training staff to maximize service delivery. Thus, mobile libraries can function more effectively in fostering a culture of literacy among elementary school students.